WMIP Model, A Resolution for Traditional Madrasah Teaching and Operation Implementation in Davao Region - Rollie C, Saprolla; Komariah, Aan (Universitas Pendidikan Indonesia, 2021)
This research aims to propose the WMIP Model or Weekend Madrasah Implementation Program as an alternative resolution for the development of Traditional Madrasah Teaching and Operation implementation in Davao Region, Philippines. The qualitative method is used as methodology, based on the interview results through madrasah education experts and implementors in the said region, Davao Region in the Philippines, other related studies results, related provisions, and laws aligned to Madrasah program in the are the instruments used in reaching the desired result. The vital points of this study are; to enhance the pedagogical skills of the asatidhs or teachers through partnership program (WMIP) and develop the firm relationship between the government schools and weekend madrasah towards the unity in education as DepEd’s vision the Education for All. The art of integration in education and this is to support the development of the country as a whole. The growth of Muslim Filipino is the benefits of the Philippines in general.